I traumi cervicali del bambino - Carbone, M.; Vittoria, F. (Lo Scalpello - Journal, 2018)
TRAUMAS OF THE CERVICAL SPINE IN CHILDREN Traumas of the cervical spine are rare in the paediatric age; however, frequently they have particular characteristics. They can be associated with neurological lesions, which include the Spinal Cord Injury WithOut Radiographic Abnormality (SCIWORA). The authors examine the anatomical and radiological features of the paediatric age responsible for the pathogenesis of fractures. They describe the most frequent clinical presentations of fractures and dislocations in this district, and recall the current indications for the correct treatment, emphasising in particular traumas that result in an indication for surgery.